Sets
Exponents and Exponential Expressions
Polynomial Arithmetic
Factoring
Rational Expressions
Radical Expressions
Functions Basics
New Functions Constructed From Old
Linear Functions
Quadratic Functions
Exponential Functions
Logarithms

Composing Functions Using Tables

Computing Compositions with Tables

Recall that composing functions is little more than taking the output of one function, then plugging it into another function as input.

We can take this same idea and apply it to functions defined by tables of values.

For example, let \(f\) and \(g\) be defined according to the table below.

\(x\)\(f(x)\)\(g(x)\)
023
154
230
302
411
545

We can find the result of, for example, \(f(g(1))\) by first finding \(g(1)=4\) and then taking that output of \(4\) and using that as input for \(f\), effectively chaining the two functions together. The final result is \(f(g(1))=f(4)=1\).

Similarly, if one wanted to compute \(g(f(2))\), we first compute \(f(2)=3\) and plug that output of \(f\) into \(g\) as input. Thus, \(g(f(2))=g(3)=2\).


A Bit of Generalization…

One can, in some cases, build a new function via composition using tables. This is done by feeding the outputs of one function into another as inputs. The table below shows the result of composing \(f\circ g\) and \(g\circ f\).

\(x\)\(f(g(x))\)\(g(f(x))\)
0\(f(g(0))=f(3)=0\)\(g(f(0))=g(2)=0\)
1\(f(g(1))=f(4)=1\)\(g(f(1))=g(5)=5\)
2\(f(g(2))=f(0)=2\)\(g(f(2))=g(3)=2\)
3\(f(g(3))=f(2)=3\)\(g(f(3))=g(0)=3\)
4\(f(g(4))=f(1)=5\)\(g(f(4))=g(1)=4\)
5\(f(g(5))=f(5)=4\)\(g(f(5))=g(4)=1\)
\(x\)\(f(x)\)\(g(x)\)
012
134
250
322
440
504

\(f(g(1))=f(4)=4\). First, find \(g(1)\), then plug the result into \(f\).

\(f(g(4))=f(0)=1\). First, find \(g(4)\), then plug the result into \(f\).

\(g(f(2))=g(5)=4\). First, find \(f(2)\), then plug the result into \(g\).

\(g(f(5))=g(0)=2\). First, find \(f(5)\), then plug the result into \(g\).

\(x\)\(h(x)\)\(g(x)\)\(h(g(x))\)\(g(h(x))\)
-101
0-1-1
122
210
\(x\)\(h(x)\)\(g(x)\)\(h(g(x))\)\(g(h(x))\)
-1012-1
0-1-101
12210
210-12
\(x\)\(h(x)\)\(g(x)\)\(h(g(x))\)\(g(h(x))\)
\(-1\)\(0\)\(1\)\(h(g(-1))=h(1)=0\)\(g(h(-1))=g(0)=-1\)
\(0\)\(-1\)\(-1\)\(h(g(0))=h(-1)=0\)\(g(h(0))=g(-1)=1\)
\(1\)\(2\)\(2\)\(h(g(1))=h(2)=1\)\(g(h(1))=g(2)=0\)
\(2\)\(1\)\(0\)\(h(g(2))=h(0)=-1\)\(g(h(2))=g(1)=2\)

To compute the \(h(g(x))\) column, we are plugging in each possible \(x\) value into \(g\) first, and then taking the output and feeding it immediately into the function \(h\).

Then, for the \(g(h(x))\) column, we plug in each possible \(x\) value into \(h\) first, then take the output of \(h\) and plug that immediately into \(g\). All of this is expressed in the table just above.

Scroll to Top